The Role of Management Staff in Developing a Safety Culture in the Healthcare Sector - Ścigaj, Mirela (Studia Oeconomica Posnaniensia, 2013)
A safety culture in the workplace can only be achieved when all the employees who make up a team have an appropriate attitude towards the issue. For this to happen, each individual employee must have such an attitude, and they must have the full support of the company’s management. And the total support for pro-safety attitudes by the management is only possible when the management themselves share this attitude. In the healthcare sector, such attitudes are particularly important because medical services are provided by people,for people.